Marqūmāt-i Imdādiyyah : yaʻnī, Qṳtb al-ʻālam ... Imdādullāh Fārūqī Mahājir Makkī ... ke maktūbāt : maʻ ifādāt-i Ḥakīmulummat Ḥa̤zrat Maulānā Ashraf ʻAlī Thānvī . - Imdādullāh Thānvī, 1817-1899 (Maktabah-yi Burhān, 1979)
Letters of an Islamic scholar; with footnotes and introduction.